Kombinasi Metode Weighted Product Dan Simple Additiveweighting Pada Sistem Pendukung Keputusan Penerimaan Calon Siswa Baru Di SMP Negeri 1 Kualuh Hilir - Sihotang, Suriani (AMIK STIEKOM SUMATERA UTARA, 2024)
Schools are educational institutions that provide formal education in the form of state schools managed by the government and private schools. SMP Negeri 1 Kualuh Hilir is the only school with a Junior High School education level in KAMPUNG MESJID which has been accredited B. The process of selecting new students at SMP Negeri 1 Kualuh Hilir has problems in terms of speed and the method used is not appropriate in selecting students. that school. Therefore, a decision support system is needed to solve the problems that occur. The Weighted Product (WP) method is a decision making method using multiplication to connect attribute ratings. The Simple Additive Weighting (SAW) method is a method used in decision making by finding the weighted sum of the performance ratings for each alternative on all attributes. By combining these two methods, it is hoped that it can help agencies in selecting participants who register at the school quickly and accurately. The final result of this research is that agencies can quickly and easily select students who meet the established criteria.